2004
DOI: 10.1021/bi0496992
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphorylation of Human Brain Glutamic Acid Decarboxylase (GAD)65 and GAD67 and Its Physiological Implications

Abstract: Previously, we reported that protein phosphorylation plays an important role in regulating soluble l-glutamic acid decarboxylase (GAD) [Bao, J. (1995) J. Biol. Chem. 270, 6464-6467] and membrane-associated GAD activity [Hsu, C. C. (1999) J. Biol. Chem. 274, 24366-24371]. Here, we report the effect of phosphorylation on the two well-defined GAD isoforms, namely, GAD65 and GAD67, using highly purified preparations of recombinant human brain GAD65 and GAD67. GAD65 was activated by phosphorylation, while GAD67 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 23 publications
2
66
0
Order By: Relevance
“…Based on these observations together with our previous observation of regulation of GAD by protein phosphorylation (18), a model leading from neuronal stimulation to regulation of GABA neurotransmission is proposed: When GABAergic neurons are stimulated, there is an increase in calcium influx (step 1). Elevation of calcium activates calpain (step 2).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Based on these observations together with our previous observation of regulation of GAD by protein phosphorylation (18), a model leading from neuronal stimulation to regulation of GABA neurotransmission is proposed: When GABAergic neurons are stimulated, there is an increase in calcium influx (step 1). Elevation of calcium activates calpain (step 2).…”
Section: Discussionmentioning
confidence: 92%
“…65 and hGAD 67 -Previously we have shown that recombinant hGAD 65 could be phosphorylated by PKCε, and hGAD 67 could be phosphorylated by PKA in vitro (18). In order to test whether GAD phosphorylation may have any effect on cleavage by μ-calpain, phos-phorylated GAD was prepared as described (18). Briefly, highly purified hGAD 67 and hGAD 65 in standard GAD buffer (50 mM KP, 1mM AET, 0.2 mM PLP, pH 7.2) were first extensively dialyzed against dialysis buffer (20 mM MOPS, 1mM AET, 0.2 mM PLP, pH 7.2).…”
Section: Calpain Cleavage Assay In Vitro-recombinant Hgadmentioning
confidence: 97%
See 2 more Smart Citations
“…Glutamate decarboxylase 1 (GAD1) is inhibited upon phosphorylation at Thr91 residue by catalytic subunit of protein kinase A while glutamate decarboxylase 2 (GAD2), is activated on phosphorylation by protein kinase C, epsilon (PRKCE). Similarly, GAD1 and GAD2 are activated by protein phosphatases which include PP1, PP2A and PPP3CA (Wei et al 2004). …”
Section: Signaling Pathways Regulating Glutamate Metabolismmentioning
confidence: 99%